On the firms' decision to hire academic scientists - Catalina Martínez; Sarah Parlane (University College Dublin, UCD School of Economics, 2018)
This paper provides a theoretical rationale for private investment in basic research. It explains the decision by some firms to hire scientists who have an intrinsic motivation to pursue academic research and allow them to do so while they also dedicate time to the firm's applied agenda. We show that this decision maximizes firms' profits in a context where basic and applied research activities are not strong substitutes and the opportunity cost, associated with deterring scientists from remaining in academia, is sufficiently low. Allowing scientists to pursue an academic agenda facilitates participation. When scientists are privately informed about their "taste for science", the contract requires that the more academically driven scientists dedicate greater attention to their personal agenda to satisfy incentive compatibility. When the reservation utility is weakly correlated with the scientist's academic inclination, this restriction has no impact and the first best contract remains optimal. But as the correlation increases, the firms tend to select less academically driven scientists. Under-investment in basic research is not triggered by the need to reduce informational rents which are non-existent as scientists face countervailing incentives. Instead it arises from the need to curb the increased cost of efforts.
Keywords: D82; D86; J31; J33; M31; 330